2010
DOI: 10.1186/1750-0680-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Combating the effects of climatic change on forests by mitigation strategies

Abstract: BackgroundForests occur across diverse biomes, each of which shows a specific composition of plant communities associated with the particular climate regimes. Predicted future climate change will have impacts on the vulnerability and productivity of forests; in some regions higher temperatures will extend the growing season and thus improve forest productivity, while changed annual precipitation patterns may show disadvantageous effects in areas, where water availability is restricted. While adaptation of fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 16 publications
3
24
1
1
Order By: Relevance
“…The results show that future development of carbon sequestration and growing stock is not only dependent on climate change scenarios but on forest management adapting to changing conditions (Matala et al 2009). Similar conclusions were drawn by Köhl et al (2010) for, among others, temperate regions in north-eastern Germany.…”
Section: Adaptive Forest Management Maysupporting
confidence: 72%
See 3 more Smart Citations
“…The results show that future development of carbon sequestration and growing stock is not only dependent on climate change scenarios but on forest management adapting to changing conditions (Matala et al 2009). Similar conclusions were drawn by Köhl et al (2010) for, among others, temperate regions in north-eastern Germany.…”
Section: Adaptive Forest Management Maysupporting
confidence: 72%
“…The results were based on changing precipitation and temperature patterns and show clear north-south differences. Overall, Köhl et al (2010) concluded that the effects of different climate change scenarios on the future productivity and species composition of German forests are minor compared to the effects of forest management. Garcio-Gonzalo et al Adaptive management requires consideration given to changing the species composition, especially when lower precipitation is expected.…”
Section: Adaptive Forest Management Ismentioning
confidence: 99%
See 2 more Smart Citations
“…Holzprodukte leisten einen nennenswerten Beitrag zur Reduzierung der CO 2 -Konzentrationen in der Atmosphäre, indem durch die stoffliche Holznutzung die natürliche Freisetzung dieses Treibhausgases durch Zersetzung verzögert wird. Außerdem substituieren Holzprodukte sowohl andere Bau-und Werkstoffe, die in der Herstellung energieintensiver sind und größere CO 2 -Emissionen verursachen, als auch als Energieholz fossile Brennstoffe (KÖHL et al 2009, RÜTER 2010. Durch den steigenden stofflichen Holzverbrauch konnten in den vergangenen Jahren bundesweit durchschnittlich 10 Mio.…”
Section: Literaturstudie Holzprodukteunclassified